Optimum Design Parameters for Heat Transfer from Triangular Fin Array within a Rectangular Enclosure - Das, Debasish; Dwivedi, Ankur; Gupta, Swati (Asian Journal of Engineering and Applied Technology, 2013)
This article outlines the evaluation of optimum parametric design for heat transfer analysis through triangular fin array within a vertically oriented rectangular enclosure using general full factorial design approach. This statistical approach has been applied to the conclusions of an experimental analysis conducted to explore the effects of fin height (L), fin spacing (S) and Rayleigh number (Ra) on free heat transfer from triangular fins attached to the heated bas plate within an air filled rectangular enclosure. The analysis of variance (ANOVA) technique has been used to find the significant effect of control parameters on response. The control parametric combination L=37.5 mm; S= 50mm; and Ra=773410 has been reported as the optimum parametric combination yielding maximum heat transfer rate for present study.